“Risk of tumor implantation in percutaneous endoscopic gastrostomy in the upper aerodigestive tumors”. Can the “non-pull” methods and the surgical approaches be definitively discarded? - Bisogni, Damiano; Fortuna, Laura; Manetti, Roberto; Talamucci, Luca; Di Marino, Michele (Acta Biomedica Atenei Parmensis, 2020)
.